Information and Reading Mediation: An Analysis of the Book “The Diary of Anne Frank” - de Oliveira, Alessandra Nunes [UNESP]; Castro, Jetur [UNESP]; de Almeida Júnior, Oswaldo Francisco [UNESP] (Universidade Federal de Santa Catarina (UFSC), 2024)
Objective: This study addresses the importance of reading the book “The Diary of Anne Frank” in the context of information mediation and reading actions carried out in educational libraries, focusing on the promotion of human rights. The study aims to highlight how this reading can contribute to critical reflection on contemporary social challenges, such as diversity, inclusion, and combating discrimination. Methods: Qualitative and exploratory research was conducted based on an interpretative approach to information mediation, reading, and critical reference. The research was grounded in a literature review, centered on the work “The Diary of Anne Frank,” conceiving the information contained in this work as an instrument of emancipatory practice. Results: It consists of fostering actions that encourage reflective reading, enabling the understanding of Anne Frank's historical context and its relevance to contemporary social issues, especially those related to diversity and human rights. The aim is to create spaces for reflection with a didactic approach focused on the critical analysis of the work, aiming to fulfill the social function of reading in libraries. Conclusions It was interpretatively understood that reading “The Diary of Anne Frank” represents a historical testimony with multiple implications for the interpreting audience. It addresses a series of relevant topics that can be discussed in the context of reading, contributing to the formation of individual perspectives and the promotion of human rights. Information mediation and reading emerge as essential tools in library practices, enabling the establishment of dialogues, the promotion of awareness, and education in libraries for the sake of human rights and critical reflection on contemporary society.
Mediação da informação e da leitura: uma análise do livro “O Diário de Anne Frank”
Keywords: Anne Frank's Diary; Information mediation; Reading mediation; World reading